Surgery and Surgery Approach Affect Survival of Patients With Stage I-IIA Small-Cell Lung Cancer: A Study Based SEER Database by Propensity Score Matching Analysis - Chen, Xiaolu; Zhu, Jia-Li; Wang, Huaying; Yu, Wanjun; Xu, Tao (Frontiers in Surgery, 2022)
Purpose: The purpose of this study was to observe the significance of surgery and its approach in stage I-IIA (according to 8th American Joint Committee on Cancer Staging Manual) small-cell lung cancer (SCLC) using the Surveillance, Epidemiology, and End Results (SEER) database. Patients and Methods: A total of 1,421 patients age 31to 93 years who were diagnosed stage I-IIA SCLC in the SEER database from 2010 to 2015 were analyzed. 1:1 propensity score matching analysis was used to minimize the effect of selection bias, and 355 pairs of patients’ data was performed subsequent statistical analysis. K-M analysis and a Cox proportional hazards model were used to observe the role of surgery and other clinical features in the patients’ prognoses on cancer-specific survival (CSS). Results: Overall, within the whole cohort, the 3- and 5-year CSS rates were 41.0% and 34.0%, respectively. In a Cox regression that adjusted for other clinical features, patients were more likely to benefit from the surgery [hazard ratio (HR) 0.292, 95% confidence interval (CI) 0.236-0.360, P < 0.001]. Unadjusted 5-year cancer-specific survival among those with surgery was 55.0%, compared with 23.0% among those without surgery. In the propensity scored-matched dataset, however, 5-year CSS among those with surgery was 54.0%, compared with 17.0% among those without surgery (HR 0.322, 95%CI 0.256-0.404, P < 0.001). In those patients received surgery, cases with lobectomy had a better 5-year CSS than those without lobectomy (65.0% vs. 39.0%). The lobectomy might be a protective factor for patients who underwent resection in CSS (HR 0.432, 95%CI 0.310-0.602, P< 0.001). Conclusions: We suggested that the surgery and lobectomy were the independent prognostic factors in SCLC patients with stage I-IIA, which even were the protective factors. If there were no surgical contraindications, we recommended that those patients should receive surgery, it was better to receive lobectomy.